Spatiotemporal Modeling of the Wind Field over an Urban Lake Subject to Wind Sheltering - Ashrafi, Mohammad; Chua, Lloyd H. C.; Irvine, K. N.; Yang, Peipei (Journal of applied meteorology and climatology, 2022)
The wind field over an urban lake may exhibit considerable variability resulting from wind-shielding effects from surrounding structures. Field measurements at an urban reservoir in Singapore were augmented by computational fluid dynamics (CFD) model results to develop a wind model over the reservoir surface via a data assimilation approach. The field measurements identified, depending on structure alignment with the prevailing wind direction, wind shielding that impacted wind direction and velocity over the reservoir surface. The wind model integrated the temporal response of the measurements and spatial distribution produced by the CFD modeling. The wind model was used to predict the spatiotemporal pattern of the wind field over the reservoir surface for a full year. The modeling results showed good agreement with measured wind data at three measurement locations on the reservoir surface. The wind model has been incorporated with a hydrodynamics and water quality model to provide the spatiotemporal wind forcing over the reservoir surface.